The Nubian pharaohs of Egypt : their lives and afterlives - Dodson, Aidan, 1962- (The American University in Cairo Press, 2023)
"The region of Nubia-now spanning the modern border between Egypt and Sudan-was long a subject of Egyptian imperial domination by its ancient pharaohs. However, in the eighth century BC matters were suddenly reversed, when the kings of Kush, the ancient name for Nubia, became the overlords of Egypt for nearly a century, before being forced to withdraw in the face of Assyrian invasions. Yet the Kushite kingdom would endure back in its heartlands for another millennium, the heritage of its Egyptian sojourn still visible in its fields of pyramid-tombs. This authoritative yet accessible book tells the story of these Nubian pharaohs of Egypt, from the origins of their kingdom of Kush, through their time as rulers of Egypt, to their heritage in the heart of Sudan-and their rediscovery in modern times. The latter uncovers some very unsavory examples of the racist attitudes of some earlier scholars. These engendered enduringly negative attitudes to aspects of careers of the Nubian pharaohs that find little support in the actual surviving evidence. The latter includes a fascinating network of texts from not only Egypt and Sudan, but also Assyria and the Bible, reflecting the interactions and conflicts of the period. There are also the standing monuments of Nubian pharaohs, ranging from temples they built throughout their dominions, to their tombs: pyramids, constructed in their ancestral heartland, in which Nubian and Egyptian funerary customs were intriguingly entangled. Richly illustrated in full color throughout, this fascinating book by a leading Egyptologist will be essential reading for anyone interested in the lives and times of Egypt's Nubian pharaohs."